Acute skin irritant effects of cyanobacteria (blue‐green algae) in healthy volunteers - Louis Pilotto; Peter Hobson; Michael D. Burch; Geetha Ranmuthugala; Robyn Attewell; Warren Weightman (Australian and New Zealand Journal of Public Health, 2004)
Abstract Objective: To assess the skin irritant potential of a range of laboratory grown cyanobacterial species using skin‐patch testing on human volunteers. Methods: Cell suspensions and extracts of cyanobacterial cultures of Microcystis aeruginosa (non‐toxic strain), Anabaena circinalis and Nodularia spumigena were applied to 64 volunteers in one trial, and Microcystis aeruginosa (toxic strain), Apanocapsa incerta and Cylindrospermopsis raciborskii were applied to 50 volunteers in a second trial. Six cell concentrations of each organism in the range from less than 5,000 to greater than 200,000 cells/ml were applied in random order using adhesive skin patches (Finn Chambers). In addition, the applications included two treatments of each cyanobacterial species, involving whole and lysed cells, and positive (sodium lauryl sulphate) and negative (culture media) controls. Patches were removed after 24 hours and assessment of erythema was made by a dermatologist blinded to the species, cell type and concentration. Results: On average, between 20% and 24% of individuals with 95% confidence interval ±8% reacted across the concentration range tested for these cyanobacterial species. The reaction rates were lower (11% to 15%) among the subset of subjects not reacting to negative controls. The reaction was mostly mild, and in all cases was resolved without treatment. This was the case for both whole and lysed cells with little difference in reaction rates between these two treatments. There was also no dose‐response across the concentration range for any of the cyanobacterial species tested. Conclusion: A small proportion of healthy people (around 20%) may develop a skin reaction to cyanobacteria in the course of normal water recreation, but the reaction is mild and resolved without treatment.